The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12871-022-01897-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of intranasal Dexmedetomidine and an oral novel formulation of Midazolam for sedation of young children during brain MRI examination: a prospective, single-center, randomized controlled trial

Abstract: Background To evaluate the safety and effectiveness of different dosages of intranasal Dexmedetomidine (DEX) in combination with oral midazolam for sedation of young children during brain MRI examination. Methods Included in this prospective single-blind randomized controlled trial were 156 children aged from 3 months to 6 years and weighing from 4 to 20 Kg with ASA I-II who underwent brain MRI examination between March 2021 and February 2022. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Recently, Gu et al 21 published a prospective single-center single-blind randomized controlled trial comparing 2 doses of dexmedetomidine 3 μg/kg versus 2 μg/kg intranasal associated with oral midazolam 0.2 mg/kg, the latter similar to ours for patients weighing more than 40 kg.…”
Section: Discussionmentioning
confidence: 55%
“…Recently, Gu et al 21 published a prospective single-center single-blind randomized controlled trial comparing 2 doses of dexmedetomidine 3 μg/kg versus 2 μg/kg intranasal associated with oral midazolam 0.2 mg/kg, the latter similar to ours for patients weighing more than 40 kg.…”
Section: Discussionmentioning
confidence: 55%
“…Undoubtedly, the e cacy of using some sedatives in combination with dexmedetomidine is better. A study by Gu H et al revealed that oral midazolam (0.2 mg/kg) with intranasal dexmedetomidine (2-3 µg/kg) might produce an excellent sedative effect for children undergoing MRI [14]. However, considering the younger age in our study, we opted to administer midazolam intranasally rather than orally because coughing and irritation may result in uncooperativeness.…”
Section: Discussionmentioning
confidence: 98%
“…Undoubtedly, the efficacy of using some sedatives in combination with dexmedetomidine is better. A study by Gu H et al revealed that oral midazolam (0.2 mg/kg) with intranasal dexmedetomidine (2–3 μg/kg) might produce an excellent sedative effect for children undergoing MRI [ 14 ]. However, considering the younger age in our study, we opted to administer midazolam intranasally rather than orally because coughing and irritation may result in uncooperativeness.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the disadvantages of midazolam and dexmedetomidine, some studies have reported the combination of the two sedatives to optimize the sedative effect. However, these studies involved the administration of dexmedetomidine intranasally plus midazolam orally [ 13 , 14 ]. In addition, this type of combination was more suitable for older children than younger children because younger children tend to be uncooperative when on an oral medication, which can cause irritation and coughing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation